Andrographolide blocks 50-kHz ultrasonic vocalizations, hyperlocomotion and oxidative stress in an animal model of mania. (July 2021) - Kanazawa, Luiz K.S.; Radulski, Débora R.; Pereira, Gabriela S.; Prickaerts, Jos; Schwarting, Rainer K.W.; Acco, Alexandra; Andreatini, Roberto
Abstract: In rats, lisdexamfetamine (LDX) induces manic-like behaviors such as hyperlocomotion and increases in appetitive 50-kHz ultrasonic vocalizations (USV), which are prevented by antimanic drugs, such as lithium. Inhibition of glycogen synthase kinase 3 beta (GSK3β) and antioxidant activity have been associated with antimanic effects. Thus, the aim of the present study was to evaluate the possible antimanic-like effects of andrographolide (ANDRO), a GSK3β inhibitor, on LDX-induced hyperlocomotion and 50-kHz USV increases. In addition, the effect of ANDRO was studied on LDX-induced oxidative stress. Lithium was used as positive control. Adult Wistar rats were treated with vehicle, lithium (100 mg/kg i.p., daily) or ANDRO (2 mg/kg i.p., 3 times a week) for 21 days. On the test day, either 10 mg/kg LDX or saline was administered i.p. and USV and locomotor activity were recorded. LDX administration increased the number of 50-kHz calls, as well as locomotor activity. Repeated treatment with lithium or ANDRO prevented these effects of LDX on 50-kHz USV and locomotor activity. LDX increased lipid peroxidation (LPO) levels in rat striatum and both lithium and ANDRO prevented this effect. LPO levels in rat striatum were positively correlated with increases in 50-kHz USV emission as well as hyperlocomotion. In conclusion, the present results indicate that ANDRO has antimanic-like effects, which may be mediated by its antioxidant properties. Highlights: Andrographolide prevented lisdexamfetamine (LDX)-induced 50-kHz ultrasonic vocalizations. Andrographolide prevented LDX-induced hyperlocomotion and striatal oxidative stress. Andrographolide has antimanic-like effect that may be mediated by its antioxidant properties.